Responsibility of the Inspectorate for the Prevention and Handling of Corruption Cases in the Region or Ministry: (Reviewed in accordance with Law Number 19 of 2019 concerning the Eradication of Corruption) - Santoso, Bambang; Haryanti, Amelia (Sinergi International Journal of Law, 2024)
This research aims to determine the role of the Inspectorate in carrying out internal oversight as an effort to detect potential corruption at the regional level. Rampant corruption at various levels of local government necessitates an active role from internal oversight institutions such as the Inspectorate. The Inspectorate serves as the frontline in preventing corruption at the local level. Consistent and effective anti-corruption efforts by the Inspectorate can positively contribute to creating a government that is clean, accountable, and serves with integrity for the welfare of the community. The role of the Inspectorate in preventing corruption at the local level is crucial in ensuring the establishment of a clean, transparent, and integrity-driven governance. As an internal oversight institution at the local level, the Inspectorate plays several strategic roles that contribute to anti-corruption efforts. This research aims to analyze the methods and strategies employed by the Inspectorate in monitoring and identifying potential corrupt practices, as well as to analyze the impact of internal oversight effectiveness on corruption prevention at the regional level. The research methodology involves documentation analysis, interviews with Inspectorate officials, and surveys of opinions from relevant stakeholders. The results of this research are expected to provide a better understanding of the Inspectorate's role in combating corruption at the local level and offer recommendations for improvements in internal oversight implementation.